Shaping infants’ social brains through vicarious social learning: the importance of positive mother–father interactions - Rousseau, Sofie; Avital, Nuphar; Tolpyhina, Yuliya (Frontiers in Psychology, 2024)
This study is the first to assess whether infants' developing social brains may be susceptible to the vicarious social experience of interparental positivity. Specifically, we explored whether infants' exposure to interparental positivity may vicariously shape their neural substrates of social development. In a sample of 45 infants (MAgeMonths= 11.01; 48.9% girls), infant left-frontal resting alpha electroencephalogram (EEG) asymmetry was derived as a reliable indicator of neural substrates linked to adaptive social development. Moreover, positive characteristics of the mother-father couple relationship were assessed both by means of observation and self-report by mother and father. In addition, various relevant covariates were assessed, including interparental negativity (observed and self-reported), as well as infants' direct caregiving experiences and duration of infant exposure to mother-father relationship-dynamics (parent-report). Results indicated that higher levels of observed interparental positivity were associated with greater infant left-frontal alpha EEG asymmetry, even after accounting for covariates (β's > 0.422). The current study's results are first to suggest that positive vicarious social experiences in infants' day-to-day lives play a significant role for early neural development.